Actinomadura harenae sp. nov., a novel actinomycete isolated from sea sand in Sanya. Issue 2 (31st October 2019) - Hu, Jiangmeihui; Han, Chuanyu; Yu, Bing; Zhao, Junwei; Guo, Xiaowei; Shen, Yue; Wang, Xiangjing; Xiang, Wensheng
Abstract : A novel actinomycete, designated strain NEAU-Ht49 T, was isolated from sea sand sampled in Sanya and characterized by using a polyphasic approach. The 16S rRNA gene sequence analysis showed that strain NEAU-Ht49 T was most closely related to Actinomadura rhizosphaerae SDA37 T (98.8 %), Actinomadura logoneensis NEAU-G17 T (98.6 %), Actinomadura oligospora ATCC 43269 T (98.6 %) and Actinomadura gamaensis NEAU-Gz5 T (98.6 %). The results of phylogenetic analysis based on the 16S rRNA gene sequences indicated that strain NEAU-Ht49 T formed a cluster with A. rhizosphaerae SDA37 T, A. logoneensis NEAU-G17 T, A. oligospora ATCC 43269 T, A. gamaensis NEAU-Gz5 T and Actinomadura rupiterrae CS5-AC15 T (96.4 %). Meso-diaminopimelic acid was detected in its cell walls and glucose, madurose, mannose and ribose were detected in whole-cell hydrolysate. The polar lipids were found to consist of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositolmannoside and two unidentified lipids. The majoy menaquinone was MK-10(H6 ) and the minor menaquinones were MK-9(H4 ) and MK-9(H8 ). The major fatty acids were C16 : 0, C18 : 1 ω9 c, 10-methyl C18 : 0 and iso-C16 : 0 . Moreover, morphological and chemotaxonomic characteristics of properties of strain NEAU-Ht49 T also confirmed the affiliation of the isolate to the genus Actinomadura . However, DNA–DNA relatedness, physiological and biochemical data showed that strain NEAU-Ht49 T could be distinguished from its closest relatives. Therefore, strain NEAU-Ht49 T represents a novel species of the genus Actinomadura, for which the name Actinomadura harenae sp. nov. is proposed, with strain NEAU-Ht49 T (=CGMCC 4.7499 T =JCM 32659 T ) as the type strain.